2020
DOI: 10.34117/bjdv6n8-179
|View full text |Cite
|
Sign up to set email alerts
|

Using Industry 4.0 Tools for Increasing Competitiveness of Clusters in Western Paraná

Abstract: Using industry 4.0 tools for increasing competitiveness of Clusters in Western ParanáUsando ferramentas da indústria 4.0 para aumentar a competitividade dos Clusters no Oeste do Paraná

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Large industrial hubs are also observed in this meso-region, such as the textile industry. In this sense, Campo Mourão is the municipality that most contributes to soybean and corn the other municipalities have characteristics of small rural properties (Alves et al, 2020).…”
Section: Forecasting Grain Production and Static Capacity Of Warehouses Using The Natural Neighbormentioning
confidence: 99%
“…Large industrial hubs are also observed in this meso-region, such as the textile industry. In this sense, Campo Mourão is the municipality that most contributes to soybean and corn the other municipalities have characteristics of small rural properties (Alves et al, 2020).…”
Section: Forecasting Grain Production and Static Capacity Of Warehouses Using The Natural Neighbormentioning
confidence: 99%
“…Recently agricultural production has grown at significant annual rates. The locational indicators of economic growth reported lack clarity regarding the information they seek to explain, thus observing the need for greater knowledge in certain regions of the state of Paraná-Brazil (Alves et al, 2020). There is an increasing number of public policies and government programs (Federal and State) that value space and state initiatives (regions), because it is in these places that economic growth and development are triggered (Lima, 2020).…”
mentioning
confidence: 99%